Integrated pest management module for cumin (Cuminum cyminum) production under arid environment - Jadon, K S; Singh, S K; Patel, Nisha; Sharma, A K (The Indian Journal of Agricultural Sciences, 2020)
Wilt (Fusarium oxysporum f. sp. cumini), Alternaria blight (Alternaria brunsii) and aphids (Myzus persicae) were recorded as major pests in cumin. A. alternata, A. brunsii and Cladosporium cladosporioides were isolated from cumin leaves and stems, Fusarium equiseti, F. oxysporum and Macrophomina phaseolina were isolated from cumin roots. Pathogenicity tests validated the disease causal organisms and molecular characterization yielded novel gene sequences and have been assigned GenBank accession numbers and released in public domain. Whereas, powdery mildew, caused by Erysiphe polygoni was also observed causing minor aerial blight. Hitherto unknown aerial blight caused by C. cladosporioides in cumin was observed for the first time. The highest seed yield with the maximum reduction of diseases and aphid population was recorded in both the varieties RZ-19 and RZ-223 from bio-intensive IPM module comprising of soil amended with neem cake and vermicompost, seeds treatment with Trichoderma viride followed by one spray of Dithane M-45 mixed with Dinocap at 45 days, one spray of Imidachloprid at 55 days and two sprays of neem oil (2%) at 50 and 60 days after sowing in prophylactic mode eventually culminated in the maximum net benefit in both the varieties RZ-19 and RZ-223 of `₹ 13722 and 11787, respectively.